Social entrepreneurship, social exchange / Norazimah Mejri - Mejri, Norazimah (Corporate Communication Unit, UiTM Mukah Campus, 2024)
The concept of ‘Social Entrepreneurship’ may seem contemporary, but its roots can be traced back through history. Although the term gained prominence only in recent decades, the essence of social entrepreneurship addressing societal issues through innovative business models has been evident across various epochs. Numerous pioneering individuals have embarked on ventures to tackle social challenges and foster positive transformations within communities.